Filmische Moderne: 60 Fragmente - Wagner, Hedwig; Nowak, Lars; Wendler, André; Fahle, Oliver; Neitzel, Britta; Wentz, Daniela; Gotto, Lisa (transcript, 2019)
Internationally renowned authors revisit films and series from 1959-2018 and show the diversity of audiovisual aesthetics in "modern film".